Materi Pendidikan Akhlak Terpuji Kitab Al-Minah Al-Saniyyah karangan Abd. Wahhab Al-Sya'rani - Fikriansyah (Idrak: Journal of Islamic Education, 2019)
Noble character is a mirror of someone's personality, besides that noble character will be able to deliver someone to high dignity. One of the attention of the Messenger of All?h Muhammad sawis to make his peopleto have good personality. A noble character can be trained by individuals so that they become characters in themselves, one of the place which can train individual to doing good morality is by education. Islamic boarding school education is an educational institution that highly upholds the morals of itsstudents.Islamic boarding school education in perpetuating moral teaching always comes from classic books, one of which is the book is Al-Minah al-Saniyyah written by Abd al-Wahhab al-Sya'rani which is a direct description of the Prophet Muhammad, who was directly nuked by author of his hadiths. Some types of akhak in it are repentance, sincerity, resignation, dzikrullah, generous and honest.